The Role of Customer Satisfaction as a Mediator for Price and Service Quality on Revisit Intention - Amroni, Amroni; Syafei, M. Yani; Narimawati, Umi (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study aims to empirically examine and analyze the effect of Price and Service Quality on Revisit Intention, with Customer Satisfaction acting as a mediating variable. The research focuses on customers of Tham-Tham Garage, a car modification workshop in Cirebon, Indonesia. A quantitative approach was used, employing a survey method via a questionnaire distributed to 140 customers who had visited the workshop at least five months prior. The data analysis utilized Partial Least Squares (PLS) with SmartPLS 3.2.8 software. The results indicate that Price has a positive and significant effect on Customer Satisfaction (β = 0.178, p = 0.045), and Service Quality also has a positive and highly significant effect on Customer Satisfaction (β = 0.715, p = 0.000). Furthermore, Customer Satisfaction significantly influences Revisit Intention. Customer Satisfaction successfully mediates the relationship between Price and Revisit Intention (β Indirect = 0.151, p = 0.046), and the relationship between Service Quality and Revisit Intention (β Indirect = 0.605, p = 0.000). The findings confirm that Customer Satisfaction is a crucial factor in driving the intention to return to the car modification service, where affordable pricing and high-quality service significantly contribute to this satisfaction.